Specific perception of the problem of tuberculosis by physicians from primary medical care - O. G. Chelnokova; M. N. Golovanova; I. G. Senin (Туберкулез и болезни лёгких, 2020)
The objective: to study the perception of the problem of tuberculosis in physicians working in primary medical care and enhance motivation to implement tuberculosis control activities.Subjects and methods. A questionnaire survey was conducted in 114 physicians from primary medical care before and after the lecture on phthisiology. A subjective assessment of the knowledge on tuberculosis (self-assessment) and results of an objective assessment were studied and compared.Results. 30% of physicians had the fear of getting infected and developing tuberculosis. The level of theoretical phthisiologic knowledge among physicians from primary medical care is insufficient; the self-assessment of this knowledge is overstated in 58.8%.